162 Investigating Strategies to Manage Feed Supply Chain Disruptions on Grow-Finish Pigs. (12th April 2022) - Miller, Kayla A; Johnson, Erika M; Matchan, Stacie; Goehring, Devin; Ross, Jason W; Gabler, Nicholas K
Abstract: In the likelihood of a foreign animal disease outbreak, the U.S. pork industry may face supply chain disruptions, including those to feed delivery. Therefore, our objective was to evaluate feeding strategies to prolonged feed availability in group housed finishing pigs and assess impacts on pig performance. 1, 407 mixed sex pigs (92±11 kg BW) were blocked by initial average BW to pens and assigned to 1 of 5 treatments (n =12 pens/treatment, 22 pigs/pen) over a 21-d test period. Treatments were fed for 14 d (P1) and thereafter all pens returned to ad libitum access to a standard commercial diet for 7 d (P2). Treatments included: 1) Pens fed ad libitum (CON); 2) Pens fed at 1.45x ME maintenance requirement daily (1.45x); 3) Pens fed 2x ME maintenance requirement daily (2x); 4) Tightened feeders to lowest setting, fed ad libitum (Closed); and 5) Whole corn kernels, fed ad libitum (Corn). The P1 and P2 BW and feed disappearance were recorded to calculate ADG, ADFI, and G:F. Data were analyzed with pen as the experimental unit and least squares means values reported by treatment. Compared with CON, 1.45x, 2x, Closed and Corn treatments significantly reduced P1 ADG (1.09 vs 0.02, 0.34, 0.72, 0.41 kg/d, respectively), ADFI (3.21 vs. 1.42, 1.90, 2.49, 2.40 kg/d, respectively) and G:F ( P < 0.05). During P2, ADG and G:F were both increased (P < 0.05) compared with CON across all treatments. However, ADFI increased only from the CON in the 2x, Closed and Corn diets (P < 0.05). Overall (d 0-21), all strategies attenuated BW, ADG and ADFI (P < 0.0001) compared with CON. However, G:F was only reduced ( P < 0.01) in 1.45x and Corn, but not 2x and Closed ( P > 0.05) from the CON. In conclusion, implementing management strategies to conserve feed maintained marginal pig growth.